Regulation of Immune Function by Polyphenols - Sujuan Ding; Hongmei Jiang; Jun Fang (Journal of Immunology Research)
Immune dysfunction is caused by various factors, including changes in relevant immune regulators and environmental stress. Immune system imbalance leads to a variety of diseases in humans. Nutrition may play an essential role in immunity by interfering with proinflammatory cytokine synthesis, immune cell regulation, and gene expression. Polyphenols, one of many categories of natural substances, exhibit a range of biological activities. Polyphenols promote immunity to foreign pathogens via various pathways. Different immune cells express multiple types of polyphenol receptors that recognise and allow cellular uptake of polyphenols, which subsequently activate signalling pathways to initiate immune responses. Furthermore, the polyphenols curcumin and epigallocatechin gallate can induce epigenetic changes in cells. In summary, polyphenols can be used to regulate intestinal mucosal immune responses, allergic diseases, and antitumour immunity.